Reversibility of surface damage induced in SiC detectors by low intensity laser plasma. (1st November 2018) - Sciuto, A.; D'Arrigo, G.; Mazzillo, M.; Torrisi, L.; Calcagno, L.
Abstract: SiC detectors based on Schottky diodes with an interdigit or a thin continuous front electrode are employed for the characterization of plasma generated by low intensity (10 10 W/cm 2 ) laser were photons, electrons and keV ions are produced. The exposure to plasma induces the formation on the detector surface of debris and/or micrometric clusters of the target material whose concentration increases with the number of laser shots, leading to the formation of nanometric film after long exposure time. The presence of this deposit strongly modifies the electrical characteristics, the optical response and ion detection properties of the detectors. In particular, we monitored the current-voltage characteristics of SiC devices and we observed an increase of the leakage current, a decrease of the Schottky barrier height and a reduction of the photon detection efficiency in the UV region, by increasing the number of plasma shots. The modification in the electrical and optical properties have been observed after a high number of laser shots, and a simple cleaning procedure allows to remove the surface deposit and, in the case of the continuous front electrode device, to restore the initial electro-optical device performances. The differences related to geometry of the front electrode are discussed.